Hot-deformed Nd-Fe-B magnets fabricated by dynamic loading with a high maximum energy product. (June 2016) - Zhang, Tieqiao; Chen, Fugang; Zheng, Yan; Wen, Hongyuan; Wang, Jing; Zhang, Lanting; Zhou, Ligang
Abstract: To enhance the degree of c-axis alignment of hot-deformed Nd-Fe-B magnets, a dynamic loading process was applied during the hot deformation process with a total thickness reduction of 75%. The effects of processing temperature on magnetic properties and texture alignment were analyzed based on the magnetic properties measurement and microstructure characterization. The extent of c-axis alignment calculated by Half-Gaussian model shows that the orientation deviation decreased to 7.9° when processed at 675 °C. This corresponds to a remanence of 1.49 T and a high maximum energy product (BH)max of 422 kJ/m 3 . The activation energy of grain growth during hot deformation is estimated to be 125.8 ± 0.2 kJ/mol. The coercivity-grain size relationship of the samples shows an increase in coercivity with decreased grain size, whose slope is consistent with a previous report. Highlights: A dynamic loading was applied during the hot deformation process of nanocrystalline Nd-Fe-B magnets. The sample hot-deformed at 675 °C shows a high remanence of 1.49 T and a high maximum energy product of 422 kJ/m 3 . The grain growth activation energy during hot deformation was determined to be 125.8 ± 0.2 kJ/mol experimentally.